Enhanced oxygen evolution at hydrous oxy-hydroxide modified iron electrodes in aqueous alkaline solution - LYONS, MICHAEL; DOYLE, RICHARD (My University, 2011)
Outstanding issues regarding the film formation and the oxygen evolution reaction (OER) electrocatalytic behaviour of multicycled iron oxyhydroxide films in aqueous alkaline solution have been revisited. The oxide is grown using a repetitive poltential multicycling technique, and the mechanism of the latter hydrous oxide formation process has been discussed. A duplex layer model of the oxide/solution interphase region is proposed. The acid/base behaviour of the hydrous oxide and the microdispersed nature of the latter material has been emphasised. The hydrous oxide is considered as a porous assembly of interlinked octahedrally coordinated anionic metal oxyhydroxide surfaquo complexes which form an open network structure. The latter contains considerable quantities of water molecules which facilitate hydroxide ion discharge at the metal site during active oxygen evolution, and also charge compensating cations. The dynamics of redox switching has been quantified via analysis of the cyclic voltammetry response as a function of potential sweep rate using the Laviron- Aoki electron hopping diffusion model by analogy with redox polymer modified electrodes. Steady state Tafel plot analysis has been used to elucidate the kinetics and mechanism of oxygen evolution. Tafel slope values of ca. 60 mVdec-1 and ca. 120 mVdec-1 are found at low and high overpotentials respectively, whereas the reaction order with respect to hydroxide ion activity changes from ca. 3/2 to ca. 1 as the potential is increased. These observations are rationalised in terms of a kinetic scheme involving Temkin adsorption and the rate determining formation of a physisorbed hydrogen peroxide intermediate on the oxide surface. The dual Tafel slope behaviour is ascribed to the potential dependence of the surface coverage of adsorbed intermediates.
PUBLISHED
Keywords: energy conversion; water electrolysis; Smart & Sustainable Planet